ANALISIS INOVASI NIK SEHAT (NIK DAN KTP ELEKTRONIK UNTUK KEMUDAHAN AKSES KESEHATAN BAGI MASYARAKAT PESERTA BPJS KESEHATAN) DUKCAPIL KEMENDAGRI DALAM PERSPEKTIF NEO-WEBERIAN STATE (NWS) - Wardani, Welly Kusuma; Wardiyanto, Bintoro (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
NIK Sehat is an innovation developed by the Directorate General of Population and Civil Registration (Dukcapil) of the Ministry of Home Affairs to support the transformation of health services administered by the Social Security Agency for Health (BPJS Kesehatan). Prior to the implementation of NIK Sehat, the integration of population data with National Health Insurance (JKN) participant data frequently posed challenges in identity verification processes. Discrepancies between electronic identity card (e-KTP) data and BPJS Kesehatan records were commonly found, and participant data validation was often difficult due to the lack of integration with Dukcapil’s population database. These issues resulted in service delays and, in some cases, denial of healthcare services. NIK Sehat is expected to improve service efficiency, reduce data inconsistencies, and ensure that JKN participants can access healthcare services using only their National Identification Number (NIK) or e-KTP. This study employs the Neo-Weberian State (NWS) perspective, which emphasizes the modernization of public administration through the strengthening of legal-rational authority, the incorporation of market-oriented values, result-oriented governance, and the utilization of technology without abandoning classical Weberian principles. The findings indicate that the NIK Sehat innovation not only enhances the administrative efficiency of healthcare services but also reinforces the role of the state as the primary provider of population data that serves as the foundation for healthcare service governance. The implications of this study highlight the need for standardized national-level implementation across local governments and healthcare facilities, the strengthening of performance-based monitoring and evaluation systems, and the development of scaling-up strategies for NIK Sehat integration as a foundation for data-driven public service development.